Approach to forming digital and organizational and technological tools for cycle management of construction reconstruction projects - OLIINYK, Valerii; ZHELEZNIAK , Vladyslav (Ways to Improve Construction Efficiency, 2025)
Development and justification of organizational and technological tools aimed at reducing the duration of restoration of reconstruction facilities that have been destroyed as a result of military operations. The goal is to create a comprehensive model that integrates the stages of work from damage assessment to commissioning, taking into account specific risks and limitations. The study is based on systems analysis methods for the decomposition of a complex reconstruction task. Network modeling methods (CPM, PERT) and graph theory are used to optimize the duration and resource planning. Simulation modeling is used to assess the effectiveness of various restoration scenarios, which allows taking into account the stochastic nature of external factors (safety, supply, financing). A structured organizational and technological tool is proposed, consisting of five consecutive stages: 1) security audit and demining; 2) technical "triage" and emergency operations; 3) prioritization and planning (according to the "Build Back Better" principle); 4) active phase of reconstruction; 5) commissioning and social reintegration. A network model has been developed that allows determining the critical path of a restoration project and identifying reserves for reducing the total duration of work. For the first time, a comprehensive toolkit has been developed that systematically links the organizational stages of post-war reconstruction with specific technological solutions and methods for optimizing duration. Unlike classical approaches to construction project management, the proposed model integrates specific risk factors characteristic of the restoration of facilities after military operations. The use of the developed toolkit will allow state authorities and construction organizations to make informed management decisions, more accurately predict the duration and cost of reconstruction, optimize the allocation of limited resources, and increase the efficiency of reconstruction projects in post-war reconstruction.